Differential Diagnosis of Amniotic Band and Intrauterine Synechiae in Second Trimester Pregnancy: Case Report - Bekir Kahveci; Yasemin Dogan; Gaye Kahveci; Muhammet Hanifi Bademkiran (Gynecology Obstetrics & Reproductive Medicine)
Amniotic band sequence (ABS) describes highly variable spectrum of congenital anomalies that occur in association with amniotic bands. İntrauterine synechiae is a condition in which scar tissue develops within the uterine cavity. We aim to present a case of ABS and a case of intrauterine synechiae and compare their ultrasonographic findings. Ultrasonography revealed contraction ring in the right groin area of the first fetus but second fetus was healthy. The diagnosis of ABS is based upon the presence of characteristic structural findings on prenatal ultrasound or postnatal physical examination. The diagnosis of intrauterine adhesions is based upon visualization of intrauterine adhesions either directly by hysteroscopy or indirectly by other imaging studies. The floor of the intrauterine adhesions is widely and lateral of the uterine cavity and occurs from four layers while the amniotic band is a thin layer and forms fluctuations in the amniotic fluid. Amniotic bands may cause variable spectrum of congenital anomalies whereas intrauterine adhesions do not increase the probability of fetal anomaly because it is out of the amniotic cavity.